The Size of Internal Auditory Canal Diverticula Is Unrelated to Degree of Hearing Loss. (24th June 2019) - Muelleman, Thomas J.; Pippin, Kaley; Shew, Matthew; Villwock, Mark; Lin, James; Quesnel, Alicia M.; Ledbetter, Luke; Staecker, Hinrich
Abstract : Objectives: To explore the relationship between hearing loss and the internal auditory canal (IAC) diverticula. To determine whether diverticula exist within or medial to the otic capsule and the prevalence in a control population. Methods: Retrospective review of adult patients with radiologic evidence of an IAC diverticulum, no evidence of otosclerosis, and audiometric testing. Analyzed degree of hearing loss and width, length, height, and volume of diverticulum. Hounsfield unit (HU) measurements lateral and medial to the diverticulum. Results: Pure tone average (PTA), air‐bone gap, and WRS (word recognition score) did not correlate with length, width, height, and volume of the diverticula. In patients with a unilateral diverticulum, there was no difference in mean PTA or WRS when comparing the diverticulum and nondiverticulum sides. Mean HU lateral to the diverticulum (2104 HU) was found to be significantly higher than medial to the diverticulum (1818 HU). There is a 5.6% prevalence of IAC diverticula in patients who underwent high‐resolution computed tomography (CT) scans for chronic sinusitis (control group). Conclusion: These data support the notion that hearing loss in this population is a product of sampling bias. The size of IAC diverticula does not correlate with the degree of hearing loss, and there is no statistically significant association between sensorineural hearing loss (SNHL) and the presence of an IAC diverticulum. IAC diverticula may exist medial to, rather than within, the otic capsule given the significant difference in mean HUs medial and lateral to the diverticula. Level of Evidence: 4 Laryngoscope, 130:1011–1015, 2020